Study of Renal Profile In Diabetic Patient at Nobel Medical College Teaching Hospital, Biratnagar (Journal of Nobel Medical College, 2016)
Background Diabetes Mellitus (DM) is one of the most common health problem characterizd by hyperglycemia. Type II Diabetes Mellitus is the most common one. Diabetic nephropathy is the most common clinical condition arises with in these patients which progressively leads to impairment in kidney’s function. Measurement of microalbumin in urine is the earliest dectactable stage of diabetic kidney disease.Material and Methods The total of 200 diabetic patients (112 males and 88 females) were enrolled and biochemical estimations including blood glucose level, serum creatinine, blood urea, urine albumin was conducted.Results Prevalance of microalbuminuria was 26 % in type II diabetic patients.Renal functions parameters like blood urea and serum ceratinine were higher in patients with positive microalbuminuria.60 % of diabetic patients are normoalbuminrics and rests 14% are proteinurics.Conclusion Various factors like increasing age, duration of diabetics, blood sugar level,blood urea, serum creatinine are the causes for microalbuminuria and proteinuria. Therefore, to rule out the early screening of diabetic kidney disease, DM patients should get routinely checked up with blood sugar level as well as renal profile test like serum creatinine, blood urea and albumin level in urine.Journal of Nobel Medical College Vol.5(2) 2016; 1-4